English rock and pop performances a sociolinguistic investigation of British and American language perceptions and attitudes - Jansen, Lisa (Linguist) (Impact, studies in language and society ;, 2022)
"This book addresses the phenomenon of non-American rock and pop singers emulating an Americanized singing style for performance purposes. By taking a novel approach to this pop cultural trend and drawing attention to the audience, British and American students' perceptions of English rock and pop performances were elicited. Interviews guided by various music clips were conducted and analyzed through a detailed qualitative content analysis. The interviewees' responses provide important insights into social meanings attached to Americanized voices and local British accents in the respective genres and show how British and American attitudes toward these performance accents differ. These perceptions and attitudes are illustrated by developing associative fields which offer a fresh view on the notion of indexicalities. An engaging folk linguistic investigation of a relatable everyday pop culture phenomenon, this book makes complex sociolinguistic phenomena easily approachable and qualitative research accessible. It is suitable for intermediate students onward and inspires further research projects in the field of language performances"--